Analisis Kualitas Pelayanan Darah Terhadap Kepuasaan Konsumen di UTD PMI Kab.Kediri - Ayu Muksin Ratna Wati; Yesy Kusumawati (PT FORMOSA CENDEKIA GLOBAL, 2022)
The purpose of this study was to identify the effect of blood service quality variables consisting of Responsiveness (Responsiveness) (X1), Assurance (Assurance) (X2), Tangible (Physical Evidence) (X3), Empathy (empathy) ( X4), and Reality (Reliability) (X5) have an influence on Consumer Satisfaction (Variable Y) at UTD PMI Kab. Kediri. This study uses a quantitative approach with data collection methods in the form of a questionnaire with a sample of 70 respondents who came to UTD PMI Kab. Kediri. The results showed that of the 5 blood service quality variables, there was 1 variable that had no effect on customer satisfaction (Y), namely the Tangible (Physical Evidence) variable (X3) and the variable that had the most influence on customer satisfaction (Y) was the Empathy variable (empathy) (X4 ).